Neuroinvasive and neurovirulent potential of SARS-CoV-2 in the acute and post-acute phase of intranasally inoculated ferrets - Feline F. W. Benavides; Edwin J. B. Veldhuis Kroeze; Lonneke Leijten; Katharina S. Schmitz; Peter van Run; Thijs Kuiken; Rory D. de Vries; Lisa Bauer; Debby van Riel (PLoS ONE, 2025)
Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) can cause systemic disease, including neurological complications, even after mild respiratory disease. Previous studies have shown that SARS-CoV-2 infection can induce neurovirulence through microglial activation in the brains of patients and experimentally inoculated animals, which are models representative for moderate to severe respiratory disease. Here, we aimed to investigate the neuroinvasive and neurovirulent potential of SARS-CoV-2 in intranasally inoculated ferrets, a model for subclinical to mild respiratory disease. The presence of viral RNA, histological lesions, virus-infected cells, and the number and surface area of microglia and astrocytes were investigated. Viral RNA was detected in various respiratory tissue samples by qPCR at 7 days post inoculation (dpi). Virus antigen was detected in the nasal turbinates of ferrets sacrificed at 7 dpi and was associated with inflammation. Viral RNA was detected in the brains of ferrets sacrificed 7 dpi, but in situ hybridization nor immunohistochemistry did confirm evidence for viral RNA or antigen in the brain. Histopathological analysis of the brains showed no evidence for an influx of inflammatory cells. Despite this, we observed an increased number of Alzheimer type II astrocytes in the hindbrains of SARS-CoV-2 inoculated ferrets. Additionally, we detected increased microglial activation in the olfactory bulb and hippocampus, and a decrease in the astrocytic activation status in the white matter and hippocampus of SARS-CoV-2 inoculated ferrets. In conclusion, although SARS-CoV-2 has limited neuroinvasive potential in this model for subclinical to mild respiratory disease, there is evidence for neurovirulent potential. This study highlights the value of this ferret model to study the neuropathogenecity of SARS-CoV-2 and reveals that a mild SARS-CoV-2 infection can affect both microglia and astrocytes in different parts of the brain.